Levine’s Conceptual Model-Based Nursing Interventions For Blood Pressure Recovery In The Elderly - Diana Pefbrianti; Devi Hairina Lestari; M. Noor Ifansyah (CV. Inara, 2023)
Hypertension becomes a problem in old age, more than 50% of people with hypertension are over 60 years old. The application of nursing theory in the provision of nursing care needs to be continuously developed. One of the theories of nursing that can be applied to the elderly who have hypertension is the Levine conservation model. Nursing actions are based on four principles: energy conservation, conservation of structural integrity, conservation of personal integrity and conservation of social integrity. The purpose of this study was to identify the effect of Levine's conceptual model-based nursing interventions on the elderly.The design of this study used quasy experiments with pre and post control groups with a large sample of 20 respondents in each group. The sampling technique used is consecutive sampling with independent variables, namely Levine model-based nursing interventions (benson relaxation techniqued, deep breath relaxation techniqued, progressive muscle relaxation technique and health education), Dependent variable in this study were sleep disorders, pain, anxiety and family support. The research instruments used are sleep quality scale (SQS), Numeric rating scale, Hamilton anxiety rating scale and family support scale. The research was carried out at the Budi Sejahtera Banjarbaru Elderly Social Protection and Rehabilitation Institution (PPRSLU). The statistical test used in this study was man whitney test. The test results found that Levine-based interventions had an effect on sleep disorders (p=0.016), but had no effect on pain (p=0.67), anxiety (p=1.00), family support (p=0.63). In elderly with hypertension, nurses need to help the elderly so that the problem of hypertension is resolved and able to fight disability. Levine-based interventions can be applied for the recovery of symptoms of hypertension.